Fuel economy improvement of a turbocharged gasoline SI engine through combining cooled EGR and high compression ratio. (15th January 2022) - Zhao, Jinxing; Fu, Rui; Wang, Sen; Xu, Hongchang; Yuan, Zhiyuan
Abstract: HEV (hybrid electric vehicles, HEV) is considered to be one of the most important automotive technical roadmaps. Fuel efficiency level of the engine used in HEV has significant impact on vehicle fuel consumption. This paper studies the performance and fuel economy potential of applying high GCR (geometrical compression ratio, GCR) and cooled EGR in turbocharged gasoline SI engines dedicated to the use in HEVs. A 1-D simulation model for a turbocharged EGR engine has been established based on a baseline 1.5T engine. Then the effects of cooled EGR and higher GCRs on engine combustion and performance have been studied and optimized. As increasing GCR from 9.7:1 to higher values that are 12.5:1 and 14:1, the full load torque decreases obviously with the maximal relative decrease of 7.6% and 21.9% respectively mainly because EGR is used to suppress the knock reducing the volumetric efficiency. The fuel economy in the most speed and load range is greatly improved mainly because of higher constant volume degree, combustion efficiency and less heat transfer and exhaust losses. In HEVs, engines mainly work in the efficient operating range, the torque reduction can be compensated by drive motor, and an appropriately high GCR is advantageous. Highlights: 1-D simulation model of turbocharged EGR engine is built. Variables optimization and turbocharger recalibration are conducted. Effects of high compression ratio and cooled EGR on combustion are analyzed. Greatly better fuel economy for turbocharged EGR engine is achieved. Guidance for development of new dedicated engine for the use in HEV.